2016
DOI: 10.1097/cji.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell–conditioned Medium Suppressed Melanoma Tumorigenicity Through the Enhancement of Natural-Killer Cellular Immunity

Abstract: Induced pluripotent stem cells (iPSCs) can secrete cytokines that are involved in T-cell development and affect cytotoxic activity. To assess the effect of iPSC-conditioned medium on tumorigenicity, we retrieved splenocytes from B6 mice and cocultured them with or without irradiated B16 melanoma cells, mouse interleukin-2 (mIL-2), or iPSC-conditioned medium. Splenocyte cytotoxicity assays against B16 melanoma cells [as cytotoxic T lymphocyte (CTL) activity] and P815 cells [as natural killer (NK) activity] were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In addition, Kawamura et al, 2016 further implied that the absence of host’s immune surveillance predisposed to the risk of tumorigenicity, whereby iPSC-derived cells were witnessed to form tumor in immunosuppressed allogeneic transplantation model [ 42 ]. These results were comparable to what Hsieh et al, 2016 reported in iPSC-conditioned medium [ 44 ]. It was also evident that tumor growth may be driven by pluripotent-associated genes [ 45 ].…”
Section: Alternative Therapeutic Strategies For Retinal Repair Usisupporting
confidence: 91%
“…In addition, Kawamura et al, 2016 further implied that the absence of host’s immune surveillance predisposed to the risk of tumorigenicity, whereby iPSC-derived cells were witnessed to form tumor in immunosuppressed allogeneic transplantation model [ 42 ]. These results were comparable to what Hsieh et al, 2016 reported in iPSC-conditioned medium [ 44 ]. It was also evident that tumor growth may be driven by pluripotent-associated genes [ 45 ].…”
Section: Alternative Therapeutic Strategies For Retinal Repair Usisupporting
confidence: 91%
“…Immunotherapy through immune checkpoint inhibition by blocking the PD-1/PD-L1 signaling pathway that enhances anti-cancer T cell immunity has shown promising and significant efficacy in a variety of malignancies, including LC [ 44 , 45 , 46 , 47 ]. Clinical trials of PD-1/PD-L1 blocking antibodies demonstrated that although PD-L1 expression levels were associated with a positive response to immunotherapy, many tumors without PD-L1 expression still responded to the treatment [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%